Easy to Read : Here Comes Kate - Level 2 - Chorao, Kay (New York : Dutton Children's Books, 2000)
In four stories, Kate, a young elephant, plays in the snow, learns to appreciate her new quilt, fusses over a lost toy, and quiets the crying of her baby cousin.
2
Keywords: Elephants -- Fiction; Family life -- Fiction; Early Reader